Diffusion of operational capabilities knowledge: The social skills perspective - Cristiane Biazzin; Mario Sacomano Neto; Silvio Eduardo Alvarez Candido (Production)
Abstract Paper aims This paper aims to understand how the social skill of managers influence the diffusion of operational capabilities in food and auto parts manufacturing networks. Originality There are taken-for-granted beliefs that its diffusion is based on replicating or transferring resources and practices from one site to another. This study is one of the first ones to discuss operational capability and socially skilled actors. Research method Two polar cases were analyzed through the Strategic Action Fields perspective based on a qualitative perspective and 17 in-depth interviews. Main findings Results demonstrate that diffusion of capability among various actors in subsidiaries will depend on a series of multidimensional factors that influence this process as the stability, state, and relationship between fields. Moreover, members tend to adopt a logic (perception of the world) that reflects the point of view of the group, and from this, the actors construct their narratives, recognize the legitimacy and justify their actions. Implications for theory and practice These perspectives have scarcely been explored in Operations management till today and shall open a new dialogue between Operations Strategy and Organization Studies. It offers practical guidance for diffusing and deploying operational capabilities.